Finite element analysis of buckling of composite-stiffened panels - Zaighami, Arash (2014)
Buckling of laminated composite plates can be improved by introducing stiffeners to the plate. Majority of the researches concentrate on the buckling response of unstiffened and stiffened panels subjected to in-plane compressive loadings. Some contributions in the form of design charts and guidelines have been developed for unstiffened panels subjected to in-plane compression and shear loadings, but still there is a relative lack of investigation into this area of research. This study considers the effects of radius of the fillet of stiffener-and-plate joint under compression loading and to investigate the effects of stiffener depth and pitch length under combined in-plane compression and shear loading using Finite Element Method (FEM). In total, 46 panels were modeled using ABAQUS software. In the first study, the effects of a filleted joint on the local and global buckling loads of the panels were investigated. The results show that increasing the radius of the fillet results in an increase in the buckling load. It had been found that 2.18% and 43.7% stability improvements are obtained for the panel with a 5-mm fillet radius in the global and local buckling, respectively. In the next study, the effects of the stiffener pitch length under combined compression and shear loading on the buckling of the panels with various plate aspect ratios were investigated numerically. The results indicate that increasing the number of stiffeners (reducing stiffener pitch length) results in an increase in the buckling load. In the last study, the effects of the height of the stiffener (stiffener depth) on the stability of the panels with different plate aspect ratios were investigated. The results show that increasing the height of the stiffeners results in the improvement of the stability of the panels. Although the improvement is significant in the panels with shorter stiffeners, this value is not noticeable after a certain value of stiffener depth.